Faktor determinan loyalitas pelanggan air minum dalam kemasan di Jabodetabek - Ariyani Ciputri; Carunia Mulya Firdausy (Universitas Tarumanagara, 2026)
This study aims to analyze the determinants of customer loyalty toward the incumbent bottled mineral water brand in the Greater Jakarta (Jabodetabek) area by examining the effects of price, brand image, and social media advertising, with sponsorship as a mediating variable. This study employed a quantitative approach using an explanatory research design. Data were collected through an online questionnaire distributed to 150 respondents who had consumed the incumbent bottled mineral water brand within the last three months using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that price and social media advertising have a positive and significant effect on customer loyalty, while brand image does not have a significant direct effect on customer loyalty. Sponsorship has a positive and significant effect on customer loyalty and mediates the relationships between price, brand image, social media advertising, and customer loyalty. These findings suggest that customer loyalty toward the market-leading bottled mineral water brand is influenced not only by functional factors such as price and digital marketing communication but also by sponsorship activities that strengthen consumers' emotional engagement with the brand. Therefore, companies should integrate competitive pricing strategies, effective social media communication, and sponsorship programs to maintain and enhance sustainable customer loyalty. Penelitian ini bertujuan untuk menganalisis faktor-faktor determinan yang memengaruhi loyalitas pelanggan terhadap merek pertahanan air minum dalam kemasan di wilayah Jabodetabek dengan menguji pengaruh harga, brand image, dan iklan media sosial serta peran sponsorship sebagai variabel mediasi. Penelitian menggunakan pendekatan kuantitatif dengan desain explanatory research. Data dikumpulkan melalui kuesioner daring kepada 150 responden yang telah mengonsumsi merek pertahanan air minum dalam kemasan dalam tiga bulan terakhir dengan teknik purposive sampling. Analisis data dilakukan menggunakan Structural Equation Modeling–Partial Least Squares (SEM-PLS). Hasil penelitian menunjukkan bahwa harga dan iklan media sosial berpengaruh positif dan signifikan terhadap loyalitas pelanggan, sedangkan brand image tidak berpengaruh signifikan secara langsung. Sponsorship berpengaruh positif dan signifikan terhadap loyalitas pelanggan serta memediasi hubungan antara harga, brand image, dan iklan media sosial terhadap loyalitas pelanggan. Temuan ini menunjukkan bahwa loyalitas pelanggan dipengaruhi tidak hanya oleh strategi harga dan komunikasi pemasaran digital, tetapi juga oleh aktivitas sponsorship yang mampu memperkuat keterikatan pelanggan terhadap merek. Oleh karena itu, perusahaan perlu mengintegrasikan strategi harga, pemasaran digital, dan program sponsorship untuk meningkatkan loyalitas pelanggan secara berkelanjutan.